Debranching Solutions in Endografting for Complex Thoracic Aortic Dissections - Goksel,Onur Selcuk (2014)
Background: Conventional surgical repair of thoracic aortic dissections is a challenge due to mortality and morbidity risks. Objectives: We analyzed our experience in hybrid aortic arch repair for complex dissections of the aortic arch. Methods: Between 2009 and 2013, 18 patients (the mean age of 67 ± 8 years-old) underwent hybrid aortic arch repair. The procedural strategy was determined on the individual patient. Results: Thirteen patients had type I repair using trifurcation and another patient with bifurcation graft. Two patients had type II repair with replacement of the ascending aorta. Two patients received extra-anatomic bypass grafting to left carotid artery allowing covering of zone 1. Stent graft deployment rate was 100%. No patients experienced stroke. One patient with total debranching of the aortic arch following an acute dissection of the proximal arch expired 3 months after TEVAR due to heart failure. There were no early to midterm endoleaks. The median follow-up was 20 ± 8 months with patency rate of 100%. Conclusion: Various debranching solutions for different complex scenarios of the aortic arch serve as less invasive procedures than conventional open surgery enabling safe and effective treatment of this highly selected subgroup of patients with complex aortic pathologies.